Implementation of the Payment Card Industry Data Security Standard in a Card Processor (Journal on studies and research of academic knowledge, 2022)
As a result of the rise in payment card fraud and identity theft, the five major payment card brands have come together to form the PCI Security Standards Council (PCI SSC). This Council developed the requirements of the Data Security Standard in the Payment Industry, in order to promote and improve the security of cardholder data and facilitate the adoption of security measures; This standard applies to all entities that store, process or transmit confidential and/or cardholder authentication data. The research approach is qualitative. The level of research proposed is exploratory and descriptive, in terms of design it will be non-experimental and cross-sectional. The analysis unit included twelve (12) employees of the Card Processor. In this work, the PCI DSS standard is implemented in a card processor, in order to strengthen the security schemes and protection of the cardholder's information. As a result of this implementation, the level of security is raised, the risk of information loss is reduced and compliance with the operability with the different means of payment brands is guaranteed.
Keywords: Payment Card Industry; Data Security Standard; PCI Security Standards Council; Cardholder; Payment cards